Quantifying regional economic impacts of CO2 intensity targets in China - Zhang, Da; Rausch, Sebastian; Karplus, Valerie J.; Zhang, Xiliang (Energy economics, 2013)
To address rising energy use and CO2 emissions, China's leadership has enacted energy and CO2 intensity targets under the Twelfth Five-Year Plan (2011-2015), which are defined at both the national and provincial levels. We develop a computable general equilibrium (CGE) model with global coverage that disaggregates China's 30 provinces and includes energy system detail, and apply it to assess the impact of the current binding provincial CO2 emissions intensity targets. We compare the impact of the provincial targets approach to a single target for China that achieves the same reduction in CO2 emissions intensity at the national level. The national target assumes trading of emissions allowances across provinces, resulting in the least-cost reductions nationwide. We find that the national target results in about 20% lower welfare loss in China relative to the provincial targets approach. Given that the regional distribution of impacts has been an important consideration in the target-setting process, we focus on the changes in provincial-level CO2 emissions intensity, CO2 emissions, energy consumption, and economic welfare. We observe significant heterogeneity across provinces in terms of the energy system response as well as the magnitude of welfare impacts. We further model the current policy of fixed end-use electricity prices in China and find that national welfare losses increase. Assumptions about capital mobility have a substantial impact on national welfare loss, while changing assumptions about the future availability of domestic natural gas resources does not have a large effect.